Partisipasi Sosial Masyarakat dalam Pengembangan Kampung Koena di Desa Wisata Gubugklakah - Ramadhanty, F.A; Sri Giriwati, N.S; Azis, S.U; Kusdiwanggo, S (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2024)
The development of tourism villages in Indonesia has progressed rapidly since the tourism sector became the country's largest foreign exchange earner. Gubugklakah Tourism Village, located in Malang Regency, is one of the villages that has utilised local potential by developing tour packages and homestays. The most significant community participation in tourism activities in Gubugklakah Village is the management of a homestay area called Koena Village. The development of Koena Village began with the PUPR program to improve the quality of houses to support the Bromo National Tourism Area, Tengger, Semeru. This study aims to determine the form of participation and the level of community participation in developing Koena Village as a homestay area in Gubugklakah Tourism Village. Qualitative descriptive methods analyse data through observation, in-depth interviews, and literature studies. The results showed that the community actively planned, implemented, and evaluated homestay development. The level of community participation is included in the interactive participation category, with the participation of energy, thoughts, skills, and materials.